2003
DOI: 10.1046/j.0001-690x.2003.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood abuse as a risk factor for psychotic experiences

Abstract: The results suggest that early childhood trauma increases the risk for positive psychotic symptoms. This finding fits well with recent models that suggest that early adversities may lead to psychological and biological changes that increase psychosis vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
404
3
19

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 677 publications
(458 citation statements)
references
References 55 publications
32
404
3
19
Order By: Relevance
“…First, lifetime parental history of psychiatric (anxiety; depression; psychosis) or substance use problems (alcohol, cannabis or other drugs) in the biological parents were assessed through self-report by participants. Second, two types of adversity during childhood were evaluated: (i) the presence of one or more of the following childhood ‘family adversities' before age 16: parental divorce, parental death and not being brought up by both parents, and (ii) a history of any ‘child abuse' before age 16: emotional, psychological, physical, and sexual abuse, using a list of examples including ignorance of one's problems, being subordinated to siblings, being beaten up and being touched or having to touch someone with a perverse intention, respectively [44,45,46,47]. Because these experiences of physical abuse may not always occur in isolation and may have an additive effect, the cumulative number of these four types of child abuse was used as the main predictor [48].…”
Section: Methodsmentioning
confidence: 99%
“…First, lifetime parental history of psychiatric (anxiety; depression; psychosis) or substance use problems (alcohol, cannabis or other drugs) in the biological parents were assessed through self-report by participants. Second, two types of adversity during childhood were evaluated: (i) the presence of one or more of the following childhood ‘family adversities' before age 16: parental divorce, parental death and not being brought up by both parents, and (ii) a history of any ‘child abuse' before age 16: emotional, psychological, physical, and sexual abuse, using a list of examples including ignorance of one's problems, being subordinated to siblings, being beaten up and being touched or having to touch someone with a perverse intention, respectively [44,45,46,47]. Because these experiences of physical abuse may not always occur in isolation and may have an additive effect, the cumulative number of these four types of child abuse was used as the main predictor [48].…”
Section: Methodsmentioning
confidence: 99%
“…These subtypes have been discussed with many psychiatrists and mental health workers with various backgrounds, both informally and during training workshops. Psychosocial research has provided some support for these groupings: it has demonstrated the impact of stimulant and hallucinogenic drugs [39], and the role of trauma [19,35] and of stress sensitivity [32] in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Bentall et al (44) found that being raped increased the odds of voice-hearing sixfold. Janssen et al (47) found child abuse prospectively predicted the development of voice-hearing, even after controlling for a family history of psychosis. This opens up an understanding of women's voice-hearing not as a symptom of madness or disease, but of a patriarchal society that attempts to control women's bodies.…”
Section: Women and Voice-hearing After The Birth Of Psychiatrymentioning
confidence: 99%